Memperkenalkan Maggot Sebagai Pakan Unggas di Kalangan Anggota Gapoktannak Aneka Karya Lombok Timur - Asnawi; Tamzil, Mohammad Hasil; Indarsih, Budi; Jaya, I Nyoman Sukartha; Haryani, Ni Ketut Dewi (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
This community service was carried out to provide insight into the maggot production system to members of Gapoktannak Aneka Karya East Lombok. The activities were executed out in collaboration between the extension team from the Poultry Production Laboratory, Faculty of Animal Husbandry, Mataram University and members of Gapoktannak Aneka Karya, East Lombok. Service activities use lecture methods, as well as discussions and questions and answers. Extension material includes the egg hatching system, maggot rearing, maggot harvesting, maggot nutritional value, and the benefits of maggots as a feed ingredient for poultry, fish and ruminants. The activity took place at the Gapoktannak Aneka Karya Meeting Hall in Mamben Daya village, Wanasaba, East Lombok from 14.00 central Indonesian time until finished. All series of community service works ran smoothly and all participants were actively involved. All participants who are members of Gapoktannak Aneka Karya appreciated activities due to they received additional knowledge about maggots, namely Black Soldier Fly (BSF) larvae which are rich in nutrients and potential feedstuff are used as feed for poultry, fish and ruminants. It is concluded that this service activity can provide new insights to participants about maggots, their benefits and rearing systems.